The Pacific Northwest disaster guide - Miller, Henry Latourette (Ooligan Press, 2024)
"Do you know the warning signs for a tsunami? Where to shelter during an earthquake? Or where your nearest designated evacuation spot is? With the increase in extreme weather, it's more important than ever to be ready for earthquakes, tsunamis, winter storms, flooding, landslides, droughts, heatwaves, and wildfires. The Pacific Northwest Disaster Guide focuses on specific natural disasters, and provides precise and helpful preparation skills through illustrations, quizzes, and guided activities fit for all ages. Learn to: Pack Go Bags and build living stockpiles. Identify natural disasters before they strike. Secure your home in case of damaging events. Plan household evacuation procedures for multiple disasters. Survive and thrive in the aftermath of catastrophe. Watch (from a safe distance) how residents of the Pacific Northwest navigate emergency situations that you could unexpectedly find yourself in, too. The Garcia-Miller family handle an earthquake, Naomi and her family avoid a tsunami, Nat and her parents work together during a winter storm, Ada and Finn stay safe during wildfire season, and many others. With the one comic that could save your life, you'll be ready to take action whenever disaster strikes"--